2006
DOI: 10.1080/09537100600745120
|View full text |Cite
|
Sign up to set email alerts
|

Lung damage may induce thrombocytopenia

Abstract: Thrombocytopenia is common in patients with lung diseases. Lung injury is associated with deranged platelet homeostasis. The potential mechanisms underlying this association were investigated in this study. The number and morphology of circulating megakaryocytes (MK) were investigated in vivo during cardiopulmonary bypass (CPB) in patients undergoing elective cardiac surgery for heart disease. The association between lung injury and thrombocytopenia was further investigated in vitro in rats with lung injury. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Specifically, the lungs of SARS patients showed diffused alveolar damage [4]. The damaged lung tissue and pulmonary endothelial cells may cause the activation and entrapment of platelets in the lungs, along with the thrombi formation at the sites of the injury, may lead to the consumption of platelets subsequently [20,21]. In addition, the lungs may also be the sites of platelet release from mature megakayocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the lungs of SARS patients showed diffused alveolar damage [4]. The damaged lung tissue and pulmonary endothelial cells may cause the activation and entrapment of platelets in the lungs, along with the thrombi formation at the sites of the injury, may lead to the consumption of platelets subsequently [20,21]. In addition, the lungs may also be the sites of platelet release from mature megakayocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lungs may also be the sites of platelet release from mature megakayocytes. In this case, the damaged lungs may result in pulmonary fibrosis and pathological changes, affecting the lung megakaryocyte fragmentation and platelet pro-duction [20,21]. Taken together, the increased consumption of platelet or/and the decreased production of platelet may lead to thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Data supporting this includes the observation that megakaryocytes are also found in pulmonary vascular beds and a higher platelet counts in postpulmonary vessels as compared to pulmonary arteries [20, 21]. In addition, more recent study shows that lung damage reduces circulating platelets, suggesting that lungs may play an active role in the regulation of platelet formation [22]. These studies suggested the presence of a pool of newly formed platelets in the pulmonary circulation.…”
mentioning
confidence: 93%
“…A study of higher platelet counts in postpulmonary vessels suggests that the lung may be a site of terminal platelet formation (Howell and Donahue, 1937). In addition, a study using rat models reveals that lung damage may reduce circulating platelets, suggesting that the lungs play an active role in the regulation of platelet formation (Xiao et al, 2006). Megakaryocyte development and platelet formation • Machlus and Italiano…”
Section: Terminal Platelet Formation and Releasementioning
confidence: 99%